Oncoplastic Surgery in Breast-Conserving Treatment: Patient Profile and Impact on Quality of Life - De Oliveira-Junior, Idam [UNESP]; Da Silva, Igor De Araujo; Da Silva, Fabíola Cristina Brandini; Da Silva, Jonathas José; Sarri, Almir José; Paiva, Carlos Eduardo; Vieira, René Aloisio Da Costa [UNESP] (Karger Publishers, 2020)
Background: Breast-conserving treatment (BCT) provides better quality of life (QL) than mastectomy without reconstruction. Oncoplastic surgery (OS) encompasses a series of surgical techniques, increasing the indications for BCT, but few studies have evaluated the impact on QL in patients who undergo BCT with OS. Materials and Methods: A prospective, cross-sectional study was conducted in women who underwent BCT. We evaluated the characteristics of patients who underwent BCT with and without OS and the associated QL. QL was assessed through the EORTC QLQ-30, EORTC QLQ-BR23, and Breast Cancer Treatment Outcome Scale (BCTOS) questionnaires. Results: A total of 300 patients underwent BCT, 72 underwent breast OS, and 37 underwent bilateral surgery. Patients who underwent OS were younger (p = 0.004), had a higher level of education (p = 0.01), had a smaller time interval since the end of treatment (p = 0.02), had tumours with greater dimensions (p = 0.003), and were more likely to receive neoadjuvant chemotherapy (p = 0.05). Based on the QL questionnaires, no difference was observed between the groups. Breast symmetry was not associated with high patient satisfaction (p = 0.55). Conclusion: Despite the fact that OS was performed in patients with worse tumour conditions and in more demanding patients, OS allowed similar cosmetic results to classical BCT.